Review of the millipede genus Levizonus Attems, 1898, with description of a new species from the Far East of Russia (Diplopoda, Polydesmida, Xystodesmidae) - Mikhaljova, Elena V. (European Journal of Taxonomy, 2021)
The genus Levizonus Attems, 1898 is rediagnosed and shown to contain eight species from Russia (Far East), North Korea, Japan and North-East China. One species is described here as new to science: Levizonus nakhodka sp. nov. A new formal synonym is proposed: Levizonus circularis Takakuwa, 1942 = Levizonus variabilis Lokschina & Golovatch, 1977 syn. nov., the valid name being the former. Levizonus circularis Takakuwa, 1942 is recorded for the fauna of China for the first time. All currently known species of Levizonus are included in a key, mapped and discussed.